Access to a Key Building Block for the Prostaglandin Family via Stereocontrolled Organocatalytic Baeyer–Villiger Oxidation. (7th May 2019) - Zhu, Kejie; Hu, Sha; Liu, Minjie; Peng, Haihui; Chen, Fen‐Er
Abstract: A new protocol for the construction of a crucial bicyclic lactone of prostaglandins using a stereocontrolled organocatalytic Baeyer–Villiger (B‐V) oxidation was developed. The key B‐V oxidation of a racemic cyclobutanone derivative with aqueous hydrogen peroxide has enabled an early‐stage construction of a bicyclic lactone skeleton in high enantiomeric excess (up to 95 %). The generated bicyclic lactone is fully primed with two desired stereocenters and enabled the synthesis of the entire family of prostaglandins according to Corey′s route. Furthermore, the reactivity and enantioselectivity of B‐V oxidation of racemic bicyclic cyclobutanones were evaluated and 90–99 % ee was obtained, representing one of the most efficient routes to chiral lactones. This study further facilitates the synthesis of prostaglandins and chiral lactone‐containing natural products to promote drug discovery. Abstract : Der Kern der Sache : Ein essenzielles bicyclisches Lacton mit zwei Stereozentren wird durch eine neue stereokontrollierte organokatalytische Baeyer‐Villiger‐Oxidation von racemischem Cyclobutanon mit wässrigem Wasserstoffperoxid synthetisiert. Dieses Schlüsselintermediat ermöglicht den Aufbau einer ganzen Familie von Prostaglandinen.